Isolation and Identification of pathogenic bacteria from drinking water from different regions in Nasseriya city from October 2014 to September 2015 - Hassan Wida’a , Qasim (University of Thi-Qar Journal of Science, 2018)
In this study isolate 134 organism from tap water at the time reaserach through the seasens winter and Sumer , to determinate pathogenic bacteria of drinking water from different regions in Nasseriya city from October 2014 to September 2015 , many people do not have access to clean and safe drinking water and many die of waterborne bacterial infections, Salmonella typhi ,Salmonella typhimurium Streptococcus faecalis ,Esherichia coli ,Aeromonas hydrophilli , Campylobacter jejuni ,Enterococcus faecalis ,Staphylococcus aureus ,Citrobacter freundii,Citrobacter diversus , Vibrio cholerae Pseudomonas aeruginosa , Helicobacter pylori , Mycobacterium avium complex, (MAC is presented, focusing on the biology and ecology of the causal agents and on the diseases‘ characteristics and their life cycles in the environment, the different city ,that contain many microbial pathogenic in tap water,the main bacteria present in human feces for example Enterobacter cloacae ,Pseudomonas aerogenosa , important sources of bacterial fecal pollution of waters are also briefly indicatedin pollution and break point in pipe line ,the aim of this study was to isolate and identify bacteria from drinking water distributions system in Nasseriya city.